Temperature regulation of polycrystalline silicon photovoltaic panels with movable thermal energy storage units filled with phase change materials - Soares, Nelson (2019)
This paper presents an experimental study to evaluate the improvement of photovoltaic (PV) performance through temperature regulation of a commercial polycrystalline silicon PV panel, by placing a movable thermal energy storage (TES) unit filled with a free-form commercial paraffin-based PCM (RT22HC) on the panel's back. The outdoor apparatus is located in Coimbra, Portugal (40.19N, 8.42W). Three identical PV panels were separately installed and individually monitored: one panel was taken as reference; the other two were considered together with a TES unit each, forming new PV/PCM systems. Regarding the TES unit, two configurations were tested: aluminum container with vertically (PV/PCM1) and horizontally (PV/PCM2) oriented rectangular cavities. The time evolution of the temperature of the PV panels was compared with each other to analyze the effective thermal regulation potential of the TES units. The time evolution of the power output was also evaluated to compare the efficiency of the different systems.